Pandemia, confinamiento y educación a distancia: una valoración universitaria en la Ciudad de México - Fernández Poncela, Anna María (2021)
This text is an approach to the student's assessment of the situation the pandemic, confinement, and in particular way distance education. The objective is to know the attitudes of young university students regarding new forms of teaching-learning, without losing sight of their state of mind, thinking and feeling about the health and social context. To achieve this objective, there are written descriptions requested from thirty students about their assessment of the surrounding situation, what they thought and what they felt. Regarding distance education, students declare satisfaction for continuing to study and frustration for social distancing. Difficulties of the massive and intensive use of digital technology, and the insistence to return to school are also revealed.